Public Awareness and Perception of Epilepsy in Bosnia & Herzegovina (B&H) - Bagić, Anto (2004)
Social stigma is one of the unfortunate realities facing persons with epilepsy. Socio-cultural differences are key determinants of this process, and diligent effort is necessary to alleviate this aspect of suffering. However, periodic public surveys in the USA have shown that despite the unchanged level of public knowledge about epilepsy over time, public attitude has improved considerably. Targeted educational campaigns aimed at further improving public attitude towards epilepsy may be designed effectively based on current public knowledge and perception of epilepsy in a given community. This study was aimed at assessing, for the first time, public knowledge and perception of epilepsy in B&H, and represents the first step towards instituting a public health awareness campaign.